2015
DOI: 10.1016/j.ecoenv.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Mercury concentrations in eggshells of the Southern Ground-Hornbill (Bucorvus leadbeateri) and Wattled Crane (Bugeranus carunculatus) in South Africa

Abstract: Highlights Total mercury concentrations in hatched eggshells of threatened birds were determined  Observed Hg levels exceeded those estimated to cause adverse reproductive effects in birds  Exposure of investigated birds to environmental Hg might be playing some contributory roles to their declining population trends. AbstractIn this study, wild hatched eggshells were collected from the nests of the threatened WattledCrane and South Ground-Hornbill in an attempt to determine total Hg concentrations. A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Despite the extremely low THg concentrations in the hardened eggshells, removing the inner membrane resulted in a stronger correlation between the THg concentration in eggshells and the THg concentration in egg contents, as well as the best overall relationship between THg concentrations in an eggshell component and the egg contents. Eggshells can be nonlethally collected in the field shortly after hatching or depredation events , and some eggshells can be collected decades after laying, as part of ornithogenic sediments . If there is any change in the composition of the eggshells based on how long the eggshell has been exposed to the environment, it could markedly influence the interpretation of temporal trends in THg concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the extremely low THg concentrations in the hardened eggshells, removing the inner membrane resulted in a stronger correlation between the THg concentration in eggshells and the THg concentration in egg contents, as well as the best overall relationship between THg concentrations in an eggshell component and the egg contents. Eggshells can be nonlethally collected in the field shortly after hatching or depredation events , and some eggshells can be collected decades after laying, as part of ornithogenic sediments . If there is any change in the composition of the eggshells based on how long the eggshell has been exposed to the environment, it could markedly influence the interpretation of temporal trends in THg concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Eggshells have been proposed as a tissue that can be nonlethally sampled after hatch to estimate Hg exposure to the developing embryo . For example, ornithogenic sediments comprised primarily of eggshells were used to examine historical trends in bird Hg exposure , and hatched eggshell fragments from endangered species were used to examine exposure when other modes of sampling were not feasible . Toxicity benchmarks have been established for Hg in egg contents , and measuring Hg in eggshells may be a means to estimate Hg concentrations in egg contents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that we did not detect Hg suggested that the studied birds foraged, probably on plants, in areas with low Hg concentrations prior to breeding. A high level of mercury in the diet was shown by Wiemeyer et al ( 1984 ) to result in fewer eggs and higher embryo mortality, and high concentrations may cause cracked eggs due to reduced eggshell strength or eggshell thinning as well as decreased embryonic growth and embryo deformities (Lundholm 1995 ; Herring et al 2010 ; Heinz et al 2012 ; Daso et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The wattled crane (Bugeranus carunculatus) is a large bird found in Africa, which populations are widely distributed in the southern Africa region, particularly in Angola, Botswana, Democratic Republic of Congo, Malawi, Mozambique, Namibia, Zambia and South Africa. Globally, wattled crane is listed as vulnerable and endangered species, under the International Union of Conservation for Nature (IUCN) Red Data List (Daso et al 2015;Fakarayi et al 2016).…”
mentioning
confidence: 99%